Teachers' Perception on the Use of Teaching Media in English Classroom - Rizka Indahyanti; Ali Wira Rahman (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study is aimed at investigating the teachers’ perception on the use of teaching media in English classroom. This study involved 25 English teachers selected from elementary school, junior high school, senior high school and vocational high school with 4-11 years of teaching experience. The instruments used in this study was questionnaire that consists of 20 items. The findings indicated that the intended perception of teachers includes the concept of applying media, the type of media used, the obstacles faced and how they arrange learning media according to the characteristics of the students. The findings also showed that the teacher prioritized aspects of appearance, usability and adjustment to learning objectives and students’ characteristics. The media they use in English language learning tends to be visual and audio-based media. Meanwhile, the use of audio-visual media still experiences obstacles in terms of mastering the technology owned by most of them. The obstacles they face in the use of learning media are related to the lack of facilities, inadequate electricity supply and internet network.